Sarcoglycan complex in masseter and sternocleidomastoid muscles of baboons: an immunohistochemical study - G. Cutroneo; A. Centofanti; F. Speciale; G. Rizzo; A. Favaloro; G. Santoro; D. Bruschetta; D. Milardi; A. Micali; D. Di Mauro; G. Vermiglio; G. Anastasi; et al. (European Journal of Histochemistry, 2015)
The sarcoglycan complex consists of a group of single-pass transmembrane glycoproteins that are essential to maintain the integrity of muscle membranes. Any mutation in each sarcoglycan gene causes a series of recessive autosomal dystrophin-positive muscular dystrophies. Negative fibres for sarcoglycans have never been found in healthy humans and animals. In this study, we have investigated whether the social ranking has an influence on the expression of sarcoglycans in the skeletal muscles of healthy baboons. Biopsies of masseter and sternocleidomastoid muscles were processed for confocal immunohistochemical detection of sarcoglycans. Our findings showed that baboons from different social rankings exhibited different sarcoglycan expression profiles. While in dominant baboons almost all muscles were stained for sarcoglycans, only 55% of muscle fibres showed a significant staining. This different expression pattern is likely to be due to the living conditions of these primates. Sarcoglycans which play a key role in muscle activity by controlling contractile forces may influence the phenotype of muscle fibres, thus determining an adaptation to functional conditions. We hypothesize that this intraspecies variation reflects an epigenetic modification of the muscular protein network that allows baboons to adapt progressively to a different social status.